The Correlation Between Students’ Big Five Personality (Introversion/Extroversion) and Learning Style. - Syahrul, Syahrul; Aulia, Andi Nurul (Universitas Pahlawan Tuanku Tambusai, 2026)
The relationship between personality and learning styles is critical for personalized education, yet findings on the introversion/extroversion and Visual-Auditory-Kinesthetic (VAK) style link remain contradictory. This quantitative study examined this correlation among 58 university students. Personality was assessed via an 8-item scale (scores 0–40), with scores ≤28 classified as introversion and ≥29 as extroversion. Learning style was measured using a 30-item VAK questionnaire. A Chi-square test of independence revealed no significant association (χ²(2) = 3.125, p .05). These results indicate that sensory learning preferences are not statistically determined by the introversion/extroversion dichotomy in this context. The study concludes that educators should move beyond personality-based style-matching and instead employ multimodal, flexible pedagogies that encourage metacognitive adaptation in diverse learners.